Dynamic changes in the skin transcriptome for the melanin pigmentation in embryonic chickens - Dong Leng; Maosen Yang; Xiaomeng Miao; Zhiying Huang; Mengmeng Li; Jia Liu; Tao Wang; Diyan Li; Chungang Feng (Poultry Science)
ABSTRACT: Dermal hyperpigmentation stands out among the various skin pigmentation phenotypes in chickens, where most other pigmentation variants affect feather color and patterning predominantly. Despite numerous black chicken breeds worldwide, only a select few exhibit comprehensive black pigmentation, which encompasses the skin, meat, flesh, and bones. The process of skin melanin pigmentation is intricate and develops successively. Historically, research has concentrated primarily on specific developmental points or stages, but fewer studies have examined the entire transcriptome across the timeline of the development of the embryo integument. In our investigation, we undertook the sequencing of chicken embryo skin samples from d 4 to d 13 of incubation. Our results showed that melanoblasts continued to migrate from E4 to the epidermis until E12. Beginning with E6, melanin was synthesized and transferred to epidermal cells and feather follicles in large quantities, and genes such as DCT, TYR, TYRP1, and MITF played a key role in this process, which is significantly different from that of white-skinned chickens. There were 854 differentially expressed genes between E7 and E8. At this stage, melanocytes formed dendritic forms and transferred melanin to keratinocytes, while the dorsal skin became visibly dark. In addition, CDH3, which is a core factor involved in a variety of biological processes, may have an important impact on skin melanin pigmentation. Collectively, our findings unveiled a phased relationship between the canonical pathway and the noncanonical pathway from E4 to E13. These analyses illuminated the gene regulatory mechanism and provided foundational data that pertained to pigmentation in chickens.